AQUATIC ETHICS SCHOOL: LEARNING TO PROTECT THE COASTAL ENVIRONMENT AT SMP NEGERI 6 BOZIHONA, IDANOGAWO DISTRICT - Anggela Opsi Yantri Gulo; Andika Taufik; Asni Putri; Sani Waruwu; Cevin Winata Mendrofa; Destalenta Trisna Laoli; Darwis Triadi; Eduard Moris Lase (Ann Publisher, 2026)
Background. Coastal areas are among the most productive ecosystems on Earth, yet they are also among the most exposed to human carelessness, particularly the steady inflow of plastic waste. Aims. This activity was carried out to build the knowledge, attitude, and moral responsibility of young people toward coastal sustainability through the